The Challenges of Upper Extremity Intramuscular Hemangioma: A Case Study and Systematic Review. Issue 2 (8th June 2022) - Abu-Ghname, Amjed; Luu, Bryan C.; Trost, Jeffrey; Raj, Sarth; Truong, Lauren; Davis, Matthew J.; Desai, Sudhen B.; Pederson, William C.; Maricevich, Marco; Maricevich, Renata S.
Abstract : Background: Intramuscular hemangiomas are rare, benign vascular tumors, constituting 0.8 percent of all hemangiomas. Upper extremity intramuscular hemangiomas pose diagnostic and therapeutic challenges because of their rarity, invasive nature, and potential for neurovascular involvement. The authors report a comprehensive systematic review of upper extremity intramuscular hemangioma management and a challenging case report. Methods: A systematic review was performed using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Electronic databases were used to identify articles describing upper extremity intramuscular hemangiomas through 2019. Patient demographics, clinical presentation, management, complications, and outcomes were reviewed. Based on operative timing, cases were categorized as either "primary" (excision performed at initial diagnosis) or "secondary" (excision performed after failure of conservative treatment). Results: Eighteen articles encompassing 25 patients were included in the authors' systematic review. Of those, 18 underwent primary excision and seven underwent secondary excision. The majority involved the forearm or antecubital region. Complete excision, evaluated by gross examination or pathology, was reported in all primary cases and 71 percent of secondary cases. Primary excisions demonstrated smaller size of mass (19.4 cm 2 versus 165.3 cm 2 ) and superior reported functional outcomes (100 percent versus 33 percent). Complications were reported in 5 percent of the primary excisions compared to 71 percent of the secondary excisions, where one complication was a fatal hematoma. Conclusions: The literature concerning upper extremity intramuscular hemangioma is limited to mostly case reports and several case series with the potential risk of bias. With careful dissection and microsurgical technique, wide local excision followed by complete reconstruction can be successfully performed at initial diagnosis for upper extremity intramuscular hemangiomas. At early stages, smaller lesion size significantly reduces the risk of functional impairment and complications.